Neurosurgical patterns of care for diffuse low-grade gliomas in Sweden between 2005 and 2015. Issue 2 (17th July 2018) - Carstam, Louise; Smits, Anja; Milos, Peter; Corell, Alba; Henriksson, Roger; Bartek, Jiri; Jakola, Asgeir Store
Abstract: Background: In the last decade, increasing evidence has evolved for early and maximal safe resection of diffuse low-grade gliomas (LGGs) regarding survival. However, changes in clinical practice are known to occur slowly and we do not know if the scientific evidence has yet resulted in changes in neurosurgical patterns of care. Methods: The Swedish Brain Tumor Registry was used to identify all patients with a first-time histopathological diagnosis of LGG between 2005 and 2015. For analysis of surgical treatment patterns, we subdivided assessed time periods into 2005-2008, 2009-2012, and 2013-2015. Population-based data on patient and disease characteristics, surgical management, and outcomes were extracted. Results: A total of 548 patients with diffuse World Health Organization grade II gliomas were identified: 142 diagnosed during 2005-2008, 244 during 2009-2012, and 162 during 2013-2015. Resection as opposed to biopsy was performed in 64.3% during 2005-2008, 74.2% during 2009-2012, and 74.1% during 2013-2015 ( P = .08). There was no difference among the 3 periods regarding overall survival ( P = .11). However, post hoc analysis of data from the 4 (out of 6) centers that covered all 3 time periods demonstrated a resection rate of 64.3% during 2005-2008, 77.4% during 2009-2012, and 75.4% during 2013-2015 ( P = .02) and longer survival of patients diagnosed 2009 and onward ( P = .04). Conclusion: In this nationwide, population-based study we observed a shift over time in favor of LGG resection. Further, a positive correlation between the more active surgical strategy and longer survival is shown, although no causality can be claimed because of possible confounding factors.